Pre-Flood Design Assessment Based on the Needs of the Jambi Community (Case Study of Three Districts / Cities) - Andy Subandi; Dwi Noerjoedianto; Andy Amir (Budapest International Research and Critics University, 2021)
The community's role during a disaster within the first 24 - 72 hours before having government's aid is crucial in making the condition under control in a timely manner, disaster management institution, especially at local level, has not had any models for preparedness training through participative approach based on the local wisdom of Jambi community to reduce disaster risks. The research process is carried out in three stages, (1) the first part is a literature study conducted to obtain information about how to deal with natural disasters, (2) Field studies conducted in several areas related to floods in Jambi Province, (3) ) Analysis Community needs are carried out by reviewing the design of the pre-disaster disaster planning system and the needs of the Flood Preparedness Community in three districts of Jambi province. A sample of 1000 people was divided into 3 groups. Each group will be completed in accordance with the pre-response system and community needs, then analyzed qualitatively. Meanwhile, to find out the management system design. Obtained preparedness data in the three villages with a total subject of 1000 people that 52.33% did not get information about the disaster or disaster preparedness, 64.6% never made an emergency plan for the family when there was a disaster, 68.67% never prepared emergency equipment (food, water, or emergency supplies), 68.27% had not attended disaster preparedness training in the past year, but only 6.2% had never discussed with neighbors about what to do in the event of a disaster. Based on the results of the research, several stages can be planned in the making of the pre-disaster assessment design as an alternative to minimize losses from disasters, which can then be developed as a disaster plan process and making mitigation in accordance with the needs of each district..